Aquabacterium pictum sp. nov., the first aerobic bacteriochlorophyll a-containing fresh water bacterium in the genus Aquabacterium of the class Betaproteobacteria. Issue 1 (3rd February 2020) - Hirose, Setsuko; Tank, Marcus; Hara, Eri; Tamaki, Hideyuki; Mori, Koji; Takaichi, Shinichi; Haruta, Shin; Hanada, Satoshi
Abstract : A strictly aerobic, bacteriochlorophyll a -containing betaproteobacterium, designated strain W35 T, was isolated from a biofilm sampled at Tama River in Japan. The non-motile and rod-shaped cells formed pink-beige pigmented colonies on agar plates containing organic compounds, and showed an in vivo absorption maximum at 871 nm in the near-infrared region, typical for the presence of bacteriochlorophyll a . The new bacterial strain is Gram-negative, and oxidase- and catalase-positive. Phylogenetic analysis based on 16S rRNA gene sequence showed that strain W35 T was closely related to species in the genus Aquabacterium . The closest phylogenetic relatives of strain W35 T were Aquabacterium commune B8 T (97.9 % sequence similarity), Aquabacterium citratiphilum B4 T (97.2 %) and Aquabacterium limnoticum ABP-4 T (97.0 %). The major cellular fatty acids were C16 : 1 ω7 c (50.4 %), C16 : 0 (22.7 %), summed feature 8 (C18 : 1 ω7 c /C18 : 1 ω6 c ; 9.7 %), C18 : 3 ω6 c (5.5 %), C12 : 0 (5.3 %) and C10 : 0 3OH (2.7 %). The respiratory quinone was ubiquinone-8. Predominant polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. The G+C content of the genomic DNA was 70.4 mol% (genome data) and 71.4 mol% (HPLC). The genome size of strain W35 T is 6.1 Mbp and average nucleotide identity analysis indicated genome similarities of strain W35 T and related Aquabacterium type strains to be 78–79 %. The results of polyphasic comparisons showed that strain W35 T was clearly distinguishable from other members of the genus Aquabacterium . Therefore, we propose a new species in the genus Aquabacterium, namely, Aquabacterium pictum sp. nov. The type strain is W35 T (=DSM 106757 T =NBRC 111963 T ). The description of the genus Aquabacterium is also emended.